Bi‐directional relay‐assisted FSO communication systems over strong turbulence channels with pointing errors. (30th July 2015) - Puri, Parul; Garg, Parul; Aggarwal, Mona
Summary: This paper presents the capacity and average bit error rate (BER)‐based performance analysis of a two‐way relay‐assisted free‐space optical communication system, over an atmospheric turbulent channel modeled by the Gamma–Gamma distribution and also affected by path loss and misalignment errors. A half‐duplex, decode‐and‐forward, two‐way, optical relay is considered, which establishes communication between two terminals, when direct communication is not possible because of non line‐of‐sight propagation or large distance. For the presented system and channel models and considering heterodyne detection at the receiver, we formulate the statistics of the instantaneous signal‐to‐noise ratio, followed by calculation of exact analytical expressions of capacity and BER. The mathematical expressions are formulated in terms of easily computable Meijer's G‐function. This mathematical analysis is accompanied with several numerical examples to illustrate the effect of the key system parameters. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper presents the capacity and average bit error rate (BER)‐based performance analysis of a two‐way relay‐assisted free space optical (TWR‐FSO) communication system, over an atmospheric turbulent channel modeled by the Gamma‐Gamma distribution and also affected by path loss and misalignment errors. For the presented system and channel models, we formulate the statistics of the instantaneous signal‐to‐noise ratio, followed by calculation of exact analytical expressions of capacity and BER in terms of easily computable Meijer's G‐function.